University teacher, potter of lives (Docentes 2.0 Journal, 2020)
The present essay argues and reflects the thought and existential feeling that around the figure of the university teacher is explained from Education, as a motivating agent and a promoter of social changes, where the praxis of the university teacher, has the ability to transform their environment, enriching the human condition of its students, because such work is much more complex than any other professional activity, since it involves developing and forming the character, intelligence and personality of the students, who will be the future professionals of the country. The university teacher brings with it a world of values, being a teacher yesterday, today and in the future has been, is and will be a huge responsibility which, at the same time, constitutes a unique privilege that we all know about teaching. The possibility of contributing to the formation of people is undoubtedly an arduous task and, why not say it, enviable, which today has real possibilities of having global reach. He who chooses the teaching profession, begins a path that is deeply marked by the ultimate goal and first priority that includes his practice: that students learn and develop. That priority involves a huge responsibility, and requires people who have great capabilities.
Keywords: Professor; University; profession